Implementation of Charaecter Education At SMP Yoannes XXIII Semarang - Rejeki, Bernadetta Sri; Khafid, Muhammad; Awalya, Awalya (Educational Management, 2021)
Character education is a very important thing to do. However, at this time it still appears that the morale of students is still in the poor category. For this reason, this study aims to determine the implementation of character education at SMP Yoannes XXIII Semarang. This research is a research that uses a qualitative approach. Data collection techniques using interviews, observation and document study. The data analysis technique in this study is an interactive model with data collection steps, data reduction, data presentation, and conclusion drawing. The results showed that the implementation of character education at SMP Yoannes XXIII Semarang was well planned and programmed, prioritizing religious values, honesty, discipline, responsibility and care, which was carried out with habituation and integrated into all subjects and extracurricular activities. The obstacles in the implementation of character education in this school are differences in understanding of the school community, limited school control, lack of parental attention and awareness of students. The supporting factors are government policies, programmed activities, a conducive situation, infrastructure, human resources, leadership and the role model of teachers. The conclusion of this research is planning for the implementation of character education at SMP Yoannes XXIII Semarang through 2 processes, namely integrated in learning activities and activities outside of learning, namely integrated in each subject and extracurricular activities, evaluation of the implementation of character education seen from the teacher assessment guidelines and books. student discipline, and there are still obstacles in the implementation of character education in this school.